Criminal responsibility of an employee who refrains from implementing administrative judicial rulings - Khlelfa, Keltoum (Milev Journal of Research and Studies, 2022)
This study Looking at the problem of great importance in the field of administrative justice represented in an indication of the impact of the failure of the criminal sanction against the administration for implementation, exploiting its authority or influence in any form was to stop the execution of the sentence or judicial administrative decision, whether this refrain from direct implementation by the competent abstained or indirectly used his power to hinder or delay the execution of the sentence or a judicial decision with an indication of whether the criminal penalty enough to ensure the implementation of the management of abstaining the protection of the rights of the convicted persons.